Virtual Classes / Mohd Faizol Haini and Ida Shaheera Azhar - Haini, Mohd Faizol; Azhar, Ida Shaheera (Faculty of Art and Design, 2021)
Virtual Classes is presented in a digital format with 1 minute duration. Animated using the Procreate app on iPad Pro and edited with Wondershare Filmora. This animation starts with text appear on a blank sheet of paper with a felt pen on the side, and when it turns to another page, it shows the current situation. The metaphor behind this is before the pandemic, everything is hands on, it is a privilege to be able to show and sketch physically. But after that, everything has changed. Virtual classes projects a visual representation of an educator juggling his task in front of the computer screen with his child in his arm. The narrative behind the dark background and the lights appear from the laptop screen portrays the current situation. This is the toughest time and it seems like there is no end to this. The only way to stay connected is talking to the screen with the help of technology. The text appears at the top telling the educator’s personal thoughts on the situation. Let’s pray and hope this soon will be over. When the MCO is finally lifted for good, let’s not forget and be more grateful with what we have.